2021
DOI: 10.1007/s00521-021-06188-z
|View full text |Cite
|
Sign up to set email alerts
|

New evaluation methods of read mapping by 17 aligners on simulated and empirical NGS data: an updated comparison of DNA- and RNA-Seq data from Illumina and Ion Torrent technologies

Abstract: During the last (15) years, improved omics sequencing technologies have expanded the scale and resolution of various biological applications, generating high-throughput datasets that require carefully chosen software tools to be processed. Therefore, following the sequencing development, bioinformatics researchers have been challenged to implement alignment algorithms for next-generation sequencing reads. However, nowadays selection of aligners based on genome characteristics is poorly studied, so our benchmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…However, the recall values between these two aligners were equally high (>0.92), except for the Novoalign Tweak 2 parameter setting that obtained an extremely low recall value of 0.79419. A previous study by Donato et al (2021) compared 17 aligners on simulated and empirical NGS data, and the findings revealed that Novoalign showed the highest accuracy in all alignments.…”
Section: Accuracy and Efficiency Of The Alignersmentioning
confidence: 94%
See 4 more Smart Citations
“…However, the recall values between these two aligners were equally high (>0.92), except for the Novoalign Tweak 2 parameter setting that obtained an extremely low recall value of 0.79419. A previous study by Donato et al (2021) compared 17 aligners on simulated and empirical NGS data, and the findings revealed that Novoalign showed the highest accuracy in all alignments.…”
Section: Accuracy and Efficiency Of The Alignersmentioning
confidence: 94%
“…In contrast to Subread, the default setting of Novoalign required more than 2 hours of runtime to obtain a comparable precision and recall. In addition, Novoalign had the longest computational time of reads mapping, probably due to its predispositions toward other parameters (Donato et al, 2021).…”
Section: Runtime and Memory Requirementsmentioning
confidence: 99%
See 3 more Smart Citations